Diagnóstico de rede urbana do Rio Grande do Sul : o caso da região funcional de planejamento nove - Martins, Marcele Salles (2009)
Changes have been occurred in the urban scenery of Brazilian cities in the last decades due to the urban growth, contributing to the occurrence of changes in the urban population profile and in the fluxes of change between urban centers. The identification of these changes subsidizes the knowledge of the formation process of the urban network, as well as it helps in the determination of the economic and territorial characteristics in the regional scope of the towns that it is composed of. In this sense, this research presents a diagnosis of the urban network of the functional region of planning nine of the state of Rio Grande do Sul - RF9, consisted of 130 towns located in the North, members of six Development Regional Council from 1985 to 2005. The methodological approach has began through the organization of the infrastructure database of the physical-territorial, socioeconomic, educational, demographic and infrastructure indicators, based on official sources. Hereafter, case studies have been accomplished in six towns, selected at each Development Regional Council, involving the institutioanl data collection with promoters, based on indicators of infrastructure, municipal legislation, environment, economy, housing and future projects. It has been found that the urban network is composed of the majority of towns with total population up to 5.000 inhabitants, which population is concentrated in the rural area. The economic participation of the majority of the towns is based on the service activity. In a general way, they show basic sanitation troubles, road access, medical service lack, income distribution disparity, high illiteracy rate, river silting, among others. With respect to the level of hierarchy and centrality, 90% of the towns that compose the RF9 have very weak level, showing the lack of specialized services provision to the population; the contrary is verified in the town of Passo Fundo, which it is the polarizer of all region. Among other towns, which present the highest levels of hierarchy, it has been found the case study towns: Erechim, Frederico Westphalen, Lagoa Vermelha, Marau, Palmeira das Missões and Soledade. The research suggests general guidelines and recommendations of planning in order to contribute to the implementation of public politics towards to the RF9 of the State of Rio Grande do Sul. Therefore, the research has confirmed the importance of the elaboration by the towns of a database that consider information of several areas, such as: infrastructure, health, education, culture, turism, housing, urban planning, environment and safety, that can be managed by able municipal technicians and that fit as support to the decision making of public managers. All actions and public politics implemented in the towns must count on the participation of the community, consider the legislation specifications, mainly the town s Master Plan and to provide better life quality to the population, searching for a sustainable urban development. So that the urban network of the RF9 raise the level of development, it is necessary the implementaçtion of improvements in the regional road mesh, the environmental management, in subsids in the agricultural diversification and in the agrindustrial production of small productors. This way, the region could increase its competitive level in the state and national scenery and, consequently, it would reach a sustainable development as well